Socialization of Terms of Use and Privacy Policy on Indonesian e-commerce Websites - Aloysius Bernanda Gunawan (Syntax Corporation Indonesia, 2020)
This article aims to identify common practices in Indonesian e-commerce regarding terms of use and privacy policies. Website visit rankings from Alexa and Similarweb were used to identify the 10 most commonly visited e-commerce sites in Indonesia. Then, placement, length, and content structure of the terms of service and privacy policies of these websites were compared. Findings suggest that the information provided by these documents is sufficient and legally compliant, although some of the websites appear to disregard their importance. The actual contents of these documents were not analyzed and are thus open for further study. The information provided in this article may give merchants intending to open e-commerce stores in Indonesia some insight into how the protection of consumers’ personal data leads to better service. This paper also proposes a simple framework for assessing the extent to which an e-commerce website successfully ensures that consumers agree and consent to its terms of use without burdening them with lengthy and obscure legal documents. Keywords: online privacy e-commerce term of use